PENELUSURAN LIRIK ISLAMI LAGU KAWIH SUNDA 'KUDU KASAHA' KARYA WINARYA ARTADINATA - Asep Solihin (LP2M ISBI Bandung, 2015)
'Kudu Kasaha' is the song title or rumpaka written by Winarya Artadinata. The theme of the lyrics conveys a mindset based on religious ideology, Islam. It's the result of the resignation facing complaints, fluctuation and uncertainty offaith. If it is listened deeply, the lyrics reminds the listeners to submit the complaints and uncertainties of faith in God Almighty. Moreover, the choice ofwords is composed in the literary mindset. The lyric of 'Kdu Kasaha', thus, isthe morals of religion and art.